Socioeconomic and cognitive determinants of smoking behavior in Indonesia: Analysis of GATS 2021 - Rahsunji Intan Nurvitasari (Public Health Risk Assesment Journal, 2026)
Background: Tobacco use remains a major public health challenge in Indonesia. This study addresses an important research gap by examining the interaction between structural determinants and cognitive-environmental reinforcements, which previous studies have largely investigated separately. By integrating the social determinants of health (SDH) and social cognitive theory (SCT) frameworks, this study examines the knowledge–behavior gap using nationally representative data from the 2021 global adult tobacco Survey (GATS) Indonesia. Methods: A cross-sectional analysis was conducted on 9,141 respondents aged ≥ 15 years. Survey-weighted multivariable logistic regression was performed to estimate adjusted odds ratios (AORs) and 95% confidence intervals (CIs), accounting for the complex multistage sampling design using the svy command in Stata 17.0. Findings: Sex was the strongest predictor of smoking; females were significantly less likely to smoke than males (AOR = 0.013; 95% CI = 0.009–0.018; p < 0.001). Higher education (AOR = 0.529) and older age (≥ 65 years; AOR = 0.419) were protective factors (p < 0.001). Exposure to tobacco promotion increased smoking likelihood (AOR = 1.249; p = 0.017). While awareness of conventional smoking risks was strongly protective (AOR = 0.367; p < 0.001), knowledge of e-cigarette health risks was not significantly associated with smoking status (p = 0.380), revealing a knowledge–behavior gap. Conclusion: Smoking behavior in Indonesia is shaped by gender norms, socioeconomic inequalities, and cognitive influences reinforced by tobacco promotion. Tobacco control strategies should extend beyond conventional risk education to address cognitive and environmental factors driving smoking behavior. Novelty/Originality of this article: This study is the first to integrate SDH and SCT using nationally representative GATS Indonesia 2021 data to jointly examine structural and cognitive determinants of smoking. It demonstrates that awareness of e-cigarette health risks does not necessarily translate into lower smoking, providing new evidence for more targeted and theory-informed tobacco control policies.